New method of the polymeric material properties experimental investigation under powerful energy flux impact. (October 2015) - Demidov, B A; Efremov, V P; Kalinin, Yu G; Kazakov, E D; Metelkin, S Yu; Petrov, V A; Potapenko, A I
Abstract: Investigation of the polymeric material properties under powerfull energy flux impact is relevant as for basic research (mathematical modeling of polymeric materials behavior in extreme conditions, testing the state equations), as for practical applications (for testing of protective coatings for space research and laboratory facilities). This paper presents the results of experimental studies of the interaction of polymeric materials with a relativistic electron beam produced by a high-current electron accelerator Calamary. Calamary facility provides a wide range of electron beam parameters: diameter 10-15 mm, the voltage on the diode up to 300 kV, the current through the diode up to 30 kA. New method of beam-target interaction area measurement was developed. The original method for the mechanical kick impulse measuring based on piezoelectric vibration sensor was presented. The dependence of the kick impulse from the power flux was obtained.